Legal Construction Analysis for Ship Chartering in Indonesia: Comparison of BIMCO Agreement and Indonesian Maritime Transport Agreement - Chandra, Capt.; Anggriani, Jum; Andreas Sapta Finady (Jurnal Smart Hukum (JSH), 2025)
This research analyzes the comparative legal construction between BIMCO standard agreements and Indonesian Sea Transportation Agreements in the context of ship chartering. Using a normative juridical method with statutory, conceptual, and comparative approaches, the research identifies fundamental divergences in the orientation and objectives of these legal instruments. BIMCO standards demonstrate a commercial global orientation with transaction flexibility and efficiency, while Indonesian Sea Transportation Agreements maintain a regulatory-national orientation focusing on domestic maritime policies. This disparity creates harmonization challenges for cross-border shipping operators, increasing transaction costs and dispute resolution complexity. This research formulates an ideal legal construction model through a selective harmonization approach with three pillars: commercial adaptability, protection of national interests, and legal certainty. Implementing this model has the potential to strengthen the competitiveness of Indonesia's shipping industry in the global maritime ecosystem and support the Global Maritime Fulcrum vision.